A bench-scale study on the recovery of magnesium sulfate (Epsom Salt) from bitterns - Pigao, Concepcion G.; Alfonso, Cecile F.; Gelera, Leonora P. (1981)
Based on the conditions and the process developed in the laboratory, this study was undertaken to further improve the technique employed and to collect data needed in the design and in the economic evaluation of subsequent bigger scale studies. The process involves the concentration of debrominated bittern to 34 Be'; the mg in solution is precipitated as MG(OH)2 by addition of NaOH; and the colloidal precipitates filtered and then dissolved using H2SO4. The resulting MgSO4 solution is filtered , concentrated by evaporation and finally cooled at 12 degrees for crystallization. A recovery of 94.4% and purity of 99.4% MgSO4 was obtained.